Pengaruh Penganggaran dan Pengendalian Intern Terhadap Akuntabilitas Keuangan Daerah pada Organisasi Perangkat Daerah Kota Gorontalo - Estin Abdullah Abdullah; Harun Blongkod; Hendra Pratama Danial (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of budgeting and internal control on regional financial accountability in Regional Apparatus Organizations (OPD) of Gorontalo City. The study employed a quantitative method with a causal research design to examine the relationship between independent and dependent variables. Data were collected through questionnaires distributed to respondents in OPD of Gorontalo City and analyzed using statistical approaches. The results indicate that budgeting has a positive and significant effect on regional financial accountability. Budgeting that is participatory, disciplined, efficient, and needs-based can improve the quality of financial accountability. In addition, internal control also has a positive and significant effect on regional financial accountability. The implementation of an effective internal control system is able to minimize the risk of irregularities, improve the reliability of financial reports, and support transparent and orderly financial management. Simultaneously, budgeting and internal control provide a significant contribution to improving regional financial accountability in OPD of Gorontalo City. This study emphasizes the importance of strengthening budgeting quality and internal control systems in realizing good and accountable governance.